Application of carbon aerogel-based materials in persulfate activation for water treatment: A review. (15th January 2023) - Shao, Binbin; Xu, Yuantao; Liu, Zhifeng; Wu, Ting; Pan, Yuan; Zhang, Xiansheng; He, Miao; Ge, Lin; Lu, Yue; Liu, Yang; Zeng, Weimin; Tang, Lin
Abstract: Recently, the sulfate radical-based advanced oxidation processes (SR-AOPs) have been widely studied and shown great potential application in water treatment. Numerous studies affirm that the persulfate (PS) can be effectively activated by carbon-based materials (CBMs), transition metal-based materials (TMBMs), light, heat, etc., to produce various active species (e.g., SO4 −, OH, 1 O2 ) and apply for pollutants removal. Among them, the carbon aerogel-based materials (CABMs) with three-dimensional (3D), low-density, and highly porous network structure have shown unique performance and advantages in PS activation for water treatment. In this review, the synthesis methods, types, and activation processes of CABMs in PS activation were comprehensively summarized and discussed first. Then, the unique properties (including structural, catalytic, and recyclable properties) of CABMs during PS activation were discussed. Besides, the effects of different operating conditions on the activation processes and the relative applications of the CABMs/PS systems in water treatment were also discussed. Lastly, the opportunities and challenges of CABMs in PS activation for water treatment were introduced and discussed. It is hoped that this review will motivate some novel inspirations for the in-depth study of this field. Highlights: Synthesis, classifications and activation processes of CABMs in PS activation were summarized. Unique properties (i.e., structural, catalytic, and recyclable properties) of CABMs during PS activation were discussed. Applications and influence factors of CABMs in PS activation for water treatment were summarized. Future challenges of using CABMs to activate PS for water treatment were proposed.